Türkiye’ de T. C. M. B. tarafından uygulanan faiz politikaları ve finans sektörüne etkileri - Ataç, Başar (My University, 2001)
I ) INTEREST POLICIES ACCORDING TO ECONOMIC SCHOOLS Classic View: The classic view is based on the Say's law and the Theory of Amount of Money. According to Say's law each supply creates its own demand. According to this theory economy will never face with the problem of unemployment and low consumption. The market will be regulated by invisible hand. Keynesian View: According to Keynesian View the level of production is being determined by the demand for good and services. The difference of Keynesian View from the classical view; according to Keynesian View the balance can also be achieved in case of deficient employment. According to Keynesian's money is demanded because of exchange, reserve and speculation motives and for this reason it was sensitive respect to the interest rate in the economy. For Keynes, economical stability cannot always be achieved via interest rates because of the liquidity trap. According to this after a certain interest rate the money demand will become insensitive against the changes in interest rates and the desired effects in the economy can not be gained. In Keynesian theory the success of monetary policy lies in, low elasticity of money demand respect to interest rates and the high elasticity of investment respect to interest rates. Monetarist View: According to monetarist view the monetary policies are more effective than the fiscal policies. Money supply is important not only in determining the price level, but also as the main factor in determining the economical activities in short run. The monetarist approach follows the classical view and it accepts that the case of deficient employment is possible and more flexible to the quantity theory. During the process of achieving full employment, an increase in money supply to extend the economical activities will directly reflect to the price level and there will be no extension in real economical activities. Neo-Classical View: In fact the neo-classical view is a variant of the monetarist approach and it accepts the political suggestions of standard monetarist view. The difference is ; Neo-Classics has reacted against the problems in market economies at technical and intellectual level and have based the monetarist theory upon technical and theoretical base. According to the hypothesis of rational expectations the individuals are evaluating the economical information with their best and making right estimations. And if the estimation fails than they do not do the same mistake again. Neo-Keynesian View: According to neo-Keynesian Theory in developing countries, because of their own special market structure, it is difficult for them to have an accumulated capital. For this reason, it is assumed that, the high interest rates given for bank accounts will be beneficial for their economical development. II) CENTRAL BANK INTEREST POLICIES There are certain ways of central bank to intervene the market. The most important of them are: * Minting * Regulating the loaning operations * Rediscount and interest rates * Disposability * Required reserve ratio Using this tools central bank tries to be effective over employment and price level. Low Interest Rates Policies: 1-) Controlling the credit interest rates via monetary extension: Monetary extension decreases the interest rates in short run and increases in long run. But if the increase in money supply is very high than the short run effect will be dominant over the long run effect. Using this method to control the interest rates is very dangerous. The fast increase in money supply will soon be effective over the price level and the high inflation will be inevitable. 2-) Controlling Interest rates by using Rediscount rates: 2-1) Selective Credit Policy According to this theory, a base credit interest rate must be determined as to prevent the banks to make loss. But the existence of some banks, which do not bankrupt although they don't determine a base interest rate, abolishes this theory. The weakest point of using this method (Selective Credit policy) the increase in the amount of cheap credits, which are borrowed by the real sector, will also increase the money supply, which may cause instability in price level. 3) Controlling the Deposit Interest rates by using the Ceiling rate System: The reason of applying ceiling rate for deposit interest rates is to prevent banks to increase the interest rates to collect more money in case of competition. This will increase the costs and cause risky banking in the market. When the ceiling interest rate is decreased owner of deposits use their money in other sectors and deposit in other institutions which are not included in the ceiling system. This will decrease the money and credit supply. The policy of indexing interest rates: The authorities of monetary policy not always try to keep the interest rates low in some particular cases the money authorities try to keep the interest rates high. These particular situations are: * Big deficit in balance of payments. * High inflation 1) Interest policies in case of big deficit in balance of payments: If the money and the capital markets are open, in this case, as to encourage foreign capital the interest rates are kept high, in case of big deficit in balance of payments in an economy. But this method is only available if the currency of the country is stable and reliable. If the currency of that country is not reliable and instable applying high interest rates to this currency may not to encourage the foreign capital. 2)Interest policies in case of high inflation: In the periods of high inflation the real income of the interests decreases, sometimes to minus values. This will discourage increase of saving and investment in middle term. Since the money is not saved or used in investment this money is used in consumption and will increase the inflation. For this reason in case of high inflation some precautions must be taken to encourage saving and investment. Applying high interest rates for deposits may be a solution to encourage saving. The Independence of Central Bank Independence of Central Bank simply means; central bank do not take orders from political authority while working on providing the stability of national currency in the economy. Creating money had always been an easy, effective and rapid way to find financial source. No government prefers to use fiscal policy, which less rapid, and hard to foresee effects and results, or limit their expenditure while there is more easy and rapid choice as minting. So creating money is the best and the easiest way to find financial source for all governments. It is seen that the actions of central bank is framed by the general economical policy of the government. If it is mentioned that in the system, government will determine the economical policy and after that Central Bank will prepare and apply a monetary policy in this frame, then it can be said that there is independency of Central Bank. But this central bank is not a central bank that is entirely apart from government. If we have a look at the views of Ali İhsan Karacan about this subject: for a while in different parts of our society we see that there are some opinions about making Turkish Republic Central Bank a more independent central bank. In other words; there had been emerged a consensus or a coalition about having a more independent central bank. If the government has accepted to make Central bank more independent than this means that this government the appropriate conditions soon will emerge. So this means that the governments will stay no longer and abandon the power. III ) INTEREST POLICIES IN TURKEY We can count the general aims of interest policies in our country as follows: * Providing price stability * The efficient distribution of bank sources * Regulations to provide development in predetermined sectors * Providing cheap credit to encourage exportation and investment * Channeling the deposit owners to fixed term deposit The most important features of this period are: the Central bank law no1715 legislated in 1930 and the central ban law, which is a regulator for previous law, no 1211 legislated in 1970. The central ban law no 1715 was insufficient for market conditions and restricting the opportunity to intervene the market. For this reason in 1970 Central bank law no 1211 was legislated. According to this law the duties of Central bank is * To apply monetary and credit policy * To take precautions to protect the value of national currency. * Open market operations and regulating the lending activities. * Discount and interest rates * Applying selective credit policies * Applying the monetary and credit policies according to the growth plans. * Giving advances to the banks * Disposability * Determining minimum required ratios The authority given to central bank for realizing the implementations that the economical program requires is an interesting point with giving important roles in applying credit and monetary policies to central bank. When we consider that the economic program is prepared by the political authority this role, which is given to central bank to intervene the economy, draws attention. In Turkey, government had always been intervening both the interest and deposit rates for public benefit until 1980. Before 1980 with a written decree of council of ministries the interest rates are always kept low as to provide cheap financial source for enterprising. Financial Liberalization After collapse of Bretton Woods Systeme in 1973 in the new economical system the economies began to liberalize rapidly and markets are opened to world. During the deregulation period between 1970 and 1980 both in the developed and non-developed countries the financial sector grew faster than the real sector and a integration between the economies has been established. We can examine the Financial Liberalization from two points: * Internal Financial Liberalization * External Financial Liberalization The internal Financial Liberalization is generally to abolish the intervention to the interest rates within the country. The external Financial Liberalization is generally is the liberalization of international capital movements. Financial Liberalization in Turkey At the end of the 1970's because of the deficit in balance of payments, decrease of national productions and the inflationist pressure the import substitution system had collapsed and as from 1980 with the leadership of private sector open growth policy began to be followed. With the decisions in 24 January government control over price ended and by time with foreign commerce and foreign exchange system the Financial Liberalization had been established both in money and credit system. The period between 1980-1983: During this period with a strict monetary policy aimed to prevent the inflationist expectations and to control the demand excess. For this reason the with decreasing the excess liquidity in the economy the increase of the price level tried to be controlled. With the policies applied as a result of this aim; there had been a real extension and a nominal decrease in increasing emission. During this period the most effective method to control the money supply was to increase the minimum required reserve ratios. Because of giving high interest rates to fixed term bank accounts there had been an increase in money supply. After the increase of exchange rates the banks had to increase the interest rates. The negative effect of this was, the small banks gave high interest rates to their costumers that they cannot afford to pay back. With all this the business chambers (since they can easily get cheap credits before) opposed to liberal interest policies and wanted government to apply ceiling interest rate policy. As a result pressure of business environments and the banker incidents, in 1982 the liberal interest policies ended and both the credits and deposits interest rates began to be determined by big banks with the control of Central Bank. The period of 1984-1989: During this period because of the increase of government financial sources and decrease of public expenditures, the deficit of the public sector had decreased. For this reason the politicians less used the source of Central bank and as a result of this there had been a serious decrease in money supply. But during the period of 1984-1987, because of the given importance to infrastructure investments of ANAP government, money supply increased significantly. During this period expansionary monetary policy applied in financial markets. But these expansionary policies criticized by the business environment. Because these policies had caused high credit interest rates and inflation. It was natural that the banks will sell the money expensively which they collect expensively. With a protocol between the treasury and the Central Bank signed in march 1989 using resource of central bank limited. As a result of this the increase of credits of Central bank slowed down. Banks had difficulty to place the funds that they have collected with high interest rates and this decreased the interest rates. The period after 1989: In 1990 Central bank declared a monetary program. According to this program it aimed limited increases in some items in its balance. The main aim of this program is to create money proportional with the foreign currency supplied from external sources. But this program could not have opportunity to be applied. As to close the deficit in balance of payments of public, central bank used very intensively. When the financial deficits of Treasury and TMO is added to the Gulf Crisis the monetary policy entirely abandoned and the populist election policies began to be applied. In 1993 as to prevent the increase of interest rates in short run the Central bank sources used instead of borrowing via adjudication. As the liquidity in the economy increased the exchange rates increased. As a result the banks bought foreign currency from abort and change this with Turkish Lira in Turkey. This caused devaluation and the system went on a crisis. The Decisions of 5 April: On 21 April 1994 a law legislated which is restricting creating money (minting) by using the resource of central bank. There was already a request of World Bank and IMF about this subject. With this law TL assets of in the balance sheet of Central bank has restricted and the balance is only permitted to enlarge in case f an increase in reserve of net currency in Central Bank's assets. As the crisis went on a few banks collapsed and as to keep the money in the system the law modified and Central Bank helped with financial support to some banks and the deposits were taken under insurance of Government. The Government went on to use the resources of Central Bank although the offered strict monetary policy in 5 april decisions and the program soon failed. 1998 Russian Crisis: The Russian crisis effected Turkey externally. During the emerge of crisis a rapid and significant amount (about 7 billion dollars) of foreign currency outflow occurred from Turkey. This caused a financial crisis in Turkey and real sector could not pay the credits to the banks. People worried about future, lost their reliance on market stop spending their money. This caused liquidity depression in the market. This depression could not tackled even with high increase (about 140%) in the expenditures of government. As a result of all these central bank and treasury injected TL about value of 6 billion dollars. November 2000 Crisis: The basic criteria of the economic program, which is supported by IMF is the Net Domestic Assets will not excess 1200 trillion. So the central bank can only inject Turkish Liras in case of foreign currency inflow. The positive effects of this program began to seen in interest rates and the overnight interest rates of Interbank. In the same period, because of some regulations about banking sector, a tendency emerged between the banks to close their deficits. So this caused prompt demand for foreign currency. This meant more liquidity and increase in interest rates. This situation forced the banks into a liquidity depression especially the ones who have bonds that will be converted into cash. After that when intranet of some banks disabled, the interest rates began to increase rapidly. For this reason foreigners sold the treasury bills and converted it to foreign currency and this caused a serious and rapid capital outflow. This event accelerated the increase of interest rates February 2001 Crisis: During the November crisis Central Bank defended the exchange rates with a very high cost. For this reason CB became vulnerable to a possible financial crisis. In proceeding February crisis the Central Bank sold 7 billion dollars. After CB finished TL funding the 6 billion of this money turned back. According to this we can say that real interest rates will be high for a while but exchange rate will be determined by exchange market. Central Bank wants to use reserves economically in consideration of a speculative attack on foreign exchange regarding IMF requests. Because Central Bank has undertaken to keep a foreign currency of minimum 12 billion dollar, that a term of minimum one years to realize the commitments. After disclosure of flouting exchange rate system the next step for Turkey is full fletched inflation targeting. For inflation targeting the markets must be sensible to interest rates. When Central Bank raise interest rate this must limit to tendency to buy foreign exchange. But markets are not enough sensible for interest rates. In fact IMF does not want inflation targeting with an uncertain market. IMF thinks that the credibility of it will be low. In any case the reliability of Turkish Republic Central Bank is tied to realizing the implementations.
Keywords: BANKACILIK-MERKEZ BANKALARI; BANKALAR VE BANKACILIK; Faiz_Türkiye